Association of maternal dietary cholesterol intake during the second and third trimesters of pregnancy and blood glucose and pregnancy outcome in women with gestational diabetes mellitus: a prospective cohort study - Xie, Cuiling; Zheng, QingXiang; Jiang, Xiumin; Liao, Yanping; Gao, Xiaoxia; Zhu, Yu; Li, Jianing; Liu, Rulin (Frontiers in Nutrition, 2024)
Background Cholesterol is essential for pregnant women to maintain maternal health and fetal support development. This study aimed to assess the cholesterol intake of women with gestational diabetes mellitus (GDM) during the second and third trimesters of pregnancy and to explore its effects on blood glucose and pregnancy outcomes. Methods This prospective cohort study collected dietary data using a food frequency questionnaire (FFQ) administered during the 24–30 gestational weeks (first survey) and the 34–42 gestational weeks (second survey). Blood glucose parameters and pregnancy outcomes were obtained from electronic medical records. Participants were divided into two groups according to the median cholesterol intake: low and high cholesterol intake groups. Results GDM women generally consumed high levels of cholesterol during pregnancy, with intake increasing in the third trimester compared to the second trimester. Compared to women with high cholesterol intake, GDM women with low cholesterol intake had a higher risk of abnormal hemoglobin A1C (HbA1C) during the second trimester [OR 26.014 (95% CI 2.616–258.727)] and the third trimester [OR 2.773 (95% CI 1.028–7.482)], as well as abnormal fasting blood glucose during the third trimester [OR 2.907 (95% CI 1.011–8.360)]. Furthermore, in the second trimester, GDM women with high cholesterol intake had higher risks of macrosomia [OR 23.195 (95% CI 2.650–203.024)] and large for gestational age (LGA) [OR 3.253 (95% CI 1.062–9.965)] but lower risks of small for gestational age (SGA) [OR 0.271 (95% CI 0.074–0.986)] compared to those with low cholesterol intake. However, in the third trimester, GDM women with high cholesterol intake had lower risks of macrosomia [OR 0.023 (95% CI 0.001–0.436)] and LGA [OR 0.199 (95% CI 0.042–0.949)]. Conclusion Cholesterol intake among GDM women during pregnancy was associated with blood glucose control and significantly influenced the risks of macrosomia, LGA, and SGA. However, LGA and SGA were also influenced by pre-pregnancy BMI, indicating cholesterol intake was one of multiple contributing factors. Limiting cholesterol intake may help GDM women better manage blood glucose levels and mitigate adverse pregnancy outcomes.